2023
DOI: 10.1002/sus2.151
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding MXene‐based macroforms for electrochemical energy storage applications

Qiongqiong Lu,
Congcong Liu,
Yirong Zhao
et al.

Abstract: Freestanding MXene‐based macroforms have gained significant attention as versatile components in electrochemical energy storage applications owing to their interconnected conductive network, strong mechanical strength, and customizable surface chemistries derived from MXene nanosheets. This comprehensive review article encompasses key aspects related to the synthesis of MXene nanosheets, strategies for structure design and surface medication, surface modification, and the diverse fabrication methods employed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 164 publications
(438 reference statements)
0
8
0
Order By: Relevance
“…The MXene's excellent conductivity ensures rapid electron transmission, making it possible to achieve high-power density supercapacitors. In the manufacturing process of electrodes, conductive agents and current collectors are not even necessary, which helps to improve the energy density of the entire device [53,54].…”
Section: Conductivitymentioning
confidence: 99%
“…The MXene's excellent conductivity ensures rapid electron transmission, making it possible to achieve high-power density supercapacitors. In the manufacturing process of electrodes, conductive agents and current collectors are not even necessary, which helps to improve the energy density of the entire device [53,54].…”
Section: Conductivitymentioning
confidence: 99%
“…Despite their ability to mimic the self-healing and appropriate electrical conductivity functions of human skin, most of the reported conductive and self-healing hydrogels cannot be directly affixed to the skin, heart, and other organs of the human body, necessitating the use of supplementary adhesive tapes and straps, thus complicating long-term practical application processes. Moreover, the nonbiodegradability and limited recyclability of conductive hydrogel strain sensors exacerbate the escalating problem of electronic waste accumulation. , MXenes, a category of two-dimensional (2D) conductive nanomaterials characterized by their significant specific surface area and presence of polarized surface-bound functional groups, have been extensively utilized in diverse domains including but not limited to electromagnetic shielding, , catalysis, , wearable electronics, energy storage, and biomedical medicine . Especially, the exceptional electrical conductivity of MXene offers a distinct advantage in fabricating highly efficient conductive networks within polymer-based hydrogels, complemented by the hydrogen bonding formed between MXene nanosheets’ surface functional groups and the polymer’s hydroxyl/carboxyl groups, conferring exceptional self-healing properties upon the hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…[32] MXene, a large family of two-dimensional (2D) transition metal carbides, carbonitrides and nitrides, [33] with high conductivity and hydrophilicity is a promising candidate as an electro-catalyst for VRFBs. [34,35] Ti 3 C 2 T x (T x stands for mixed surface terminations) was the first [36] and most widely studied MXene for a range of applications. [34,[37][38][39] A few studies of the use of HF (hydrofluoric acid)-etched MXene's for VRFB have been reported.…”
Section: Introductionmentioning
confidence: 99%